One year after on Tyrrhenian coasts: The ban of cotton buds does not reduce their dominance in beach litter composition. (September 2022) - Poeta, G.; Bazzichetto, M.; Gallitelli, L.; Garzia, M.; Aprea, F.; Bartoli, F.; Battisti, C.; Cascone, S.; Corradi, A.; D'Amelia, D.; D'Amico, E.; De Luca, J.; et al.
Abstract: In January 2019, Italy banned the sale of plastic cotton buds, which is one of the most abundant litter items entering the sea and then washing ashore. However, since the ban came into force, no studies have been carried out to assess whether the measure has actually led to the reduction of plastic cotton buds accumulating on Italian coasts. Here we aim at evaluating the effectiveness of the ban in reducing the amount of cotton buds reaching sandy beaches of the Tyrrhenian coast. Specifically, we monitored the accumulation of beach litter for one year since the ban came into force. By surveying eight coastal sites from winter 2019 to winter 2020, we collected a total of 52, 824 items mostly constituted by plastic debris (97.6%). We found that cotton buds were the most abundant item (42.3% of total litter), followed by plastic (28.5%) and polystyrene (5.43%) fragments. Our preliminary assessment suggests that the ban has so far not led to a sensible reduction in the amount of cotton buds entering the marine ecosystem. This was to be expected since implementation strategies are still lacking (i.e. no economic sanctions can be imposed in case of non-compliance) and bans are differently implemented among countries facing the Mediterranean Sea, calling for law enforcement and implementation at the national and international levels. Highlights: 97.6% of the 52, 849 collected beach litter items were made of plastic. Cotton buds, plastic and polystyrene pieces were the most abundant items. The abundance of beach litter varied seasonally and across sites. The ban on plastic cotton buds did not reduce their amount on Tyrrhenian coasts.